Exploring the Isaiah scrolls and their textual variants - Parry, Donald W., (Studia Post Biblica;, 2019)
In Exploring the Isaiah Scrolls and Their Textual Variants, Donald W. Parry systematically presents, on a verse-by-verse basis, the variants of the Hebrew witnesses of Isaiah (the Masoretic Text and the twenty-one Isaiah Dead Sea Scrolls) and briefly discusses why each variant exists. The Isaiah scrolls have greatly impacted our understanding of the textual history of the Bible, and in recent decades, Bible translation committees have incorporated a number of the variants into their translations; as such, the Isaiah scrolls are important for both academic and popular audiences. Variant characterizations include four categories: (a) accidental errors, e.g., dittography, haplography, metathesis, graphic similarity; (b) intentional changes by scribes and copyists; (c) synonymous readings; (d) scribes' stylistic approaches and conventions.